Anti-oxidation water-based lubricating coating material for hot extrusion as well as preparation method and application of anti-oxidation water-based lubricating coating material

By providing an anti-oxidation water-based lubricating coating material for hot extrusion composed of base powder, deionized water and active additives, the problems of environmental pollution, high cost and complex processes that traditional lubrication methods exist in the hot extrusion production of zirconium and zirconium alloys are solved, and efficient, environmentally friendly and high-quality lubricating effects are achieved.

CN119875408APending Publication Date: 2025-04-25XIAN WESTERN ENERGY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411962647.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The traditional lubrication methods used in the hot extrusion production of zirconium and zirconium alloys in the prior art have problems of environmental pollution, high costs and complex processes, and cannot meet the needs of high efficiency, environmental protection and high-quality output.

Method used

A water-based lubricating coating material for hot extrusion is provided, which consists of a base powder, deionized water and an active additive, wherein the base powder comprises graphite powder, molybdenum disulfide powder, silica, alumina and other components. The active additive includes a wetting agent, a dispersing agent, a defoaming agent and an antioxidant, and is formed by a specific weight ratio compound.

Benefits of technology

The lubricating coating material exhibits excellent lubricating effect under a high temperature environment of 500°C to 800°C, significantly reducing friction factors, avoiding smoke pollution during heating of traditional lubricants, reducing production costs, and meeting the high efficiency, environmental protection and high-quality output requirements of hot extrusion of zirconium and zirconium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875408A_ABST
    Figure CN119875408A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricants, and particularly discloses an anti-oxidation water-based lubricating coating material for hot extrusion and a preparation method and application thereof, and the anti-oxidation water-based lubricating coating material for hot extrusion is composed of basic powder, deionized water and an active auxiliary agent according to a weight ratio of (37.6-48.2): (49.1-58.6): (1.3-11.7). Wherein the basic powder is formed by mixing graphite powder, molybdenum disulfide powder, silicon dioxide, aluminum oxide, potassium oxide, sodium oxide and sodium silicate powder according to a specific proportion; the active auxiliary agent is prepared from a wetting agent, a dispersing agent, a defoaming agent and an antioxidant according to a corresponding proportion. The raw materials of the lubricating coating material are easy to obtain, the preparation process is simple, the lubricating coating material is not prone to falling off after being coated on a blank and has certain strength, meanwhile, reaction with the surrounding atmosphere can be reduced during heating, good thermal protection can be provided after the blank is discharged from a furnace, the friction coefficient of zirconium and zirconium alloy can be effectively reduced during hot extrusion, and the service life of the lubricating coating material is prolonged. And the inner and outer surface quality of an extruded product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lubricant technology, specifically relating to an anti-oxidation water-based lubricating coating material for hot extrusion, its preparation method, and its application. Background Technology

[0002] In the nuclear industry, zirconium and zirconium alloys are widely used in the manufacture of nuclear-grade rods, tubes, and profiles due to their excellent nuclear properties, particularly their small thermal neutron absorption interface. Hot extrusion is the primary processing method for achieving large-scale production. During the extrusion of zirconium and zirconium alloys, lubrication is crucial. A suitable lubricant can significantly reduce peak extrusion pressure, greatly alleviate friction and wear on the die, and thus extend the service life of the tools and dies. Furthermore, good lubrication helps improve the yield rate, reduce the generation of defective and scrap products, and improve the surface quality of the finished products, resulting in significant cost reduction and efficiency improvement.

[0003] However, there are currently no water-based lubricants specifically designed for hot extrusion of zirconium and zirconium alloys on the market. In actual production, companies have to resort to traditional lubrication methods, namely coating the surface of zirconium and zirconium alloy ingots with copper foil and using lubricants such as graphite, asphalt, and cylinder oil. Although this method can provide some lubrication at extrusion temperatures of 500℃ to 800℃, contributing to extended die life and improved surface quality of extruded products, it has the following drawbacks from a long-term development and overall benefit perspective: Firstly, the mixture of asphalt, graphite, and cylinder oil used in copper-clad extrusion generates a large amount of fumes when heated, causing serious environmental pollution and harm, which is inconsistent with the current green and environmentally friendly industrial development concept; secondly, the copper foil itself is expensive, significantly increasing production costs, and the copper-cladding process is extremely cumbersome and complex, resulting in low production efficiency. Furthermore, the removal of residual copper foil from the surface of extruded products is extremely difficult, not only increasing subsequent processing steps and costs, but also potentially affecting product quality if not handled properly.

[0004] In conclusion, with the continuous advancement of industrial technology and increasingly stringent environmental regulations, there is an urgent need for a new type of lubricant that can replace copper-coated lubricant during extrusion in the 500℃~800℃ range.

[0005] In view of this, this invention is hereby proposed. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide an anti-oxidation water-based lubricating coating material for hot extrusion and its application. It mainly addresses the environmental pollution, high cost, and complex process caused by the traditional method of coating copper and using lubricants such as graphite, asphalt, and cylinder oil in the hot extrusion of zirconium and zirconium alloys. These problems prevent it from meeting the requirements of high efficiency, environmental protection, and high-quality output in the hot extrusion of zirconium and zirconium alloys.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] In a first aspect, the present invention provides an anti-oxidation water-based lubricating coating material for hot extrusion, the anti-oxidation water-based lubricating coating material for hot extrusion being composed of a base powder, deionized water and an active additive, wherein the weight ratio of the base powder, deionized water and active additive is (37.6-48.2):(49.1-58.6):(1.3-11.7).

[0009] Furthermore, the base powder is composed of the following components by weight percentage:

[0010] (1) 22.8% to 37.2% graphite powder;

[0011] (2) 12.8%–23.7% molybdenum disulfide powder;

[0012] (3) 16.9%–28.6% silicon dioxide;

[0013] (4) 11.3% to 20.5% alumina

[0014] (5) 2.6% to 9.3% potassium oxide and sodium oxide;

[0015] (6) Sodium silicate powder of 14.6% to 21.9%;

[0016] The graphite powder has a particle size of 500-2000 mesh, the molybdenum disulfide powder has a particle size of 1000-2000 mesh, the silicon dioxide has a particle size of 800-1500 mesh, and the sodium silicate powder has a modulus of 2.0-2.8.

[0017] Preferably, the base powder is composed of the following components by weight percentage:

[0018] (1) 23% to 33% graphite powder;

[0019] (2) 13%–17% molybdenum disulfide powder;

[0020] (3) 17%–23% silicon dioxide;

[0021] (4) 13%–17% aluminum oxide

[0022] (5) 3% to 6% potassium oxide and sodium oxide;

[0023] (6) 16% to 21% sodium silicate powder.

[0024] Furthermore, the active adjuvant is composed of the following components by weight percentage:

[0025] (1) 29.3% to 46.5% wetting agent;

[0026] (2) 31.9% to 41.4% dispersant;

[0027] (3) 11.9% to 21.4% defoamer;

[0028] (4) 7.3% to 16.8% antioxidants.

[0029] Preferably, the active adjuvant is composed of the following components by weight percentage:

[0030] (1) 30% to 33% wetting agent;

[0031] (2) 33%–41% dispersant;

[0032] (3) 12% to 21% defoamer;

[0033] (4) 14% to 16% antioxidants.

[0034] Further, the wetting agent comprises the following components: sodium hydroxide, amide compounds, and sodium dodecyl sulfate or sodium dibutyl sulfonate, wherein the weight ratio of sodium hydroxide, amide compounds, and sodium dodecyl sulfate or sodium dibutyl sulfonate is (20.1–43.2):(18.7–35.1):(23.6–44.5).

[0035] The dispersant comprises the following components: an ammonium salt solution of modified styrene-maleic acid copolymer, sodium carboxymethyl cellulose or acrylate copolymer, and sodium dodecylbenzenesulfonate or polysulfonate, wherein the weight ratio of the ammonium salt solution of modified styrene-maleic acid copolymer, sodium carboxymethyl cellulose or acrylate copolymer to sodium dodecylbenzenesulfonate or polysulfonate is (34.3-52.6):(11.5-21.9):(27.8-44.2);

[0036] The defoamer comprises the following components: carboxyl amide defoamer, polyoxyethylene ether, and silicone defoamer, wherein the weight ratio of the carboxyl amide defoamer, polyoxyethylene ether, and silicone defoamer is (17.6–33.2): (15.2–21.7): (22.8–51.3).

[0037] The antioxidant comprises the following components: sodium thiosulfate, water-soluble L-ascorbic acid, and disodium ethylenediaminetetraacetate or sodium pyrophosphate, wherein the weight ratio of sodium thiosulfate, water-soluble L-ascorbic acid, and disodium ethylenediaminetetraacetate or sodium pyrophosphate is (33.6–58.2):(14.8–28.4):(23.4–43.1).

[0038] Secondly, the present invention also provides a method for preparing the above-mentioned anti-oxidation water-based lubricating coating material for hot extrusion, comprising the following steps:

[0039] Step 1: Synthesis of the base powder: Weigh out 22.8%–37.2% graphite powder, 12.8%–23.7% molybdenum disulfide powder, 16.9%–28.6% silicon dioxide, 11.3%–20.5% aluminum oxide, 2.6%–9.3% potassium oxide and sodium oxide, and 14.6%–21.9% sodium silicate powder as raw materials according to weight percentage; then homogenize the above raw materials to obtain the base powder.

[0040] Step 2, Preparation of active additives: Weigh out 29.3%–46.5% of wetting agent, 31.9%–41.4% of dispersant, 11.9%–21.4% of defoamer, and 7.3%–16.8% of antioxidant as raw materials according to weight percentage; then homogenize the above raw materials to obtain the active additives;

[0041] Step 3, Preparation of lubricating coating material: After heating deionized water to a set temperature, add the base powder synthesized in step 1 and perform homogenization treatment. At the same time, add the active additive prepared in step 2 during the homogenization treatment. During the homogenization treatment, control the weight ratio of the base powder, deionized water and active additive to be (37.6~48.2):(49.1~58.6):(1.3~11.7). After homogenization, thoroughly stir and mix the obtained liquid. After stirring, allow it to cool naturally to room temperature to obtain the above-mentioned anti-oxidation water-based lubricating coating material for hot extrusion.

[0042] Furthermore, in step 1, a three-dimensional mixer is used to homogenize the base powder, and the spindle speed of the three-dimensional mixer is set to 10 rpm to 24 rpm, and the stirring time is set to 1 h to 3 h.

[0043] Furthermore, in step 2, the active additive is homogenized using a top-mounted electric stirrer, with the stirring speed set to 50 rpm to 200 rpm and the stirring time set to 5 min to 10 min.

[0044] Furthermore, in step 3, the deionized water used has a resistivity of 0.5 MΩ to 18 MΩ at room temperature and is heated to 55°C to 95°C.

[0045] The homogenization process uses a homogenizer, the speed of which is set to 15,000 rpm to 20,000 rpm, and the homogenization is carried out for more than or equal to 30 minutes.

[0046] After homogenization, the resulting liquid is transferred to an electric dispersing mixer for stirring. The speed of the electric dispersing mixer is set to 100 rpm to 500 rpm, and the stirring time is set to 2 h to 4 h.

[0047] Furthermore, in step 3, during the homogenization process, the active additive is added in several batches, specifically every 5 to 10 minutes, and the amount of the active additive added at one time does not exceed one-third of its total weight.

[0048] Thirdly, the present invention also provides the application of the above-mentioned anti-oxidation water-based lubricating coating material for hot extrusion, or the anti-oxidation water-based lubricating coating material for hot extrusion prepared by the above-mentioned preparation method, in the hot extrusion preparation of zirconium and zirconium alloy rods, tubes and profiles.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] The hot extrusion anti-oxidation water-based lubricating coating material provided by this invention is formed by compounding a base powder, deionized water, and active additives in a specific weight ratio. The base powder contains various components with specific particle size ranges, such as graphite powder, molybdenum disulfide powder, silicon dioxide, alumina, potassium oxide, sodium oxide, and sodium silicate powder. These components work synergistically. Graphite powder, with its excellent lubrication properties, effectively reduces the coefficient of friction between the metal and the die during high-temperature extrusion, reducing energy loss and die wear. Molybdenum disulfide powder further enhances the lubrication effect; its unique layered structure helps form a stable lubricating film, maintaining good lubrication performance even under high pressure and high temperature environments. Silica and alumina help improve the coating's hardness and wear resistance, making the coating less prone to breakage under high extrusion pressure. The coating is degraded, thus better protecting the surface of zirconium and zirconium alloys; potassium oxide and sodium oxide can adjust the melting point and fluidity of the coating to a certain extent, so that it can maintain good adhesion and appropriate fluidity at high temperatures, and continuously provide lubrication for the extrusion process; sodium silicate powder dissolves in deionized water during stirring to form sodium silicate aqueous solution, which has a certain binding and stabilizing effect on the base powder, coating the base powder, and after coating and drying, a dense SiO2 film can be formed on the outermost layer to isolate the external protective metal. The addition of active additives effectively reduces the viscosity of the solution, improves the leveling of the coating, and ensures that the components are evenly dispersed and form a stable coating structure. Compared to traditional methods of using copper-clad sheets with lubricants such as graphite, asphalt, and cylinder oil, the lubricating coating material of this invention, due to its water-based system, avoids the problem of generating large amounts of harmful fumes when traditional lubricants are heated, significantly reducing environmental pollution. Furthermore, practical verification has shown that its friction coefficient reaches 0.193–0.212 under high-temperature environments of 500℃–800℃ using a rotary friction and wear tester, demonstrating its excellent lubrication effect. It also possesses high fluidity, high adhesion, and good oxidation resistance, fully meeting the requirements of nuclear-grade zirconium and zirconium alloy hot extrusion production. In addition, the raw materials used in this invention are all commercially available, and the formulation is relatively simple. Compared to traditional copper-clad sheet lubricants, the cost is reduced by 50%–60%, providing enterprises with a competitive edge in the market. Attached Figure Description

[0051] The accompanying drawings are incorporated in and form part of this specification, and together with the description serve to explain the principles of the invention.

[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0053] Figure 1 This is a flowchart of the preparation method of the anti-oxidation water-based lubricating coating material for hot extrusion according to the present invention;

[0054] Figure 2 This is a friction coefficient test curve obtained by using a rotary friction and wear tester at 500℃~800℃ after preparing pure zirconium tubes, based on the lubricating coating material obtained in Example 1 of this invention.

[0055] Figure 3 This is a cross-sectional height data diagram of the wear marks corresponding to the three-dimensional scanning of the lubricating coating material obtained in Example 1 of the present invention after the preparation of pure zirconium tubes;

[0056] Figure 4 This is a 3D scan of the three-dimensional wear marks of the lubricating coating material obtained in Example 1 of the present invention after the preparation of pure zirconium tubing;

[0057] Figure 5 This is a top view of the wear marks on the lubricating coating material obtained in Example 1 of the present invention after the preparation of pure zirconium tubing;

[0058] Figure 6 These are actual images of the inner and outer surfaces of a pure zirconium tube prepared after the actual application of the lubricating coating material in Embodiment 1 of the present invention.

[0059] Figure 7 These are actual images of the inner and outer surfaces of Zr-4 pipes prepared after the actual application of the lubricating coating material in Embodiment 2 of the present invention.

[0060] Figure 8 This is a photograph of the outer surface of a Zr-4 rod prepared after the actual application of the lubricating coating material in Example 3 of this invention. Detailed Implementation

[0061] Exemplary embodiments will now be described in detail. The embodiments described below are not representative of all embodiments consistent with this invention. Rather, they are merely examples consistent with some aspects of the invention as detailed in the appended claims.

[0062] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0063] This invention provides an anti-oxidation water-based lubricating coating material for hot extrusion, primarily targeting applications involving zirconium and zirconium alloys during extrusion processing in the 500℃~800℃ range. Within this temperature range, the microstructure and properties of zirconium and zirconium alloys are highly sensitive to changes in the processing environment. Traditional lubricating materials often struggle to simultaneously provide both anti-oxidation and lubrication performance. However, the lubricating coating material of this invention stands out due to its innovative water-based formulation system. Using deionized water as the base medium, it not only possesses excellent fluidity and wettability, enabling it to uniformly cover the surface of the billet, but also offers numerous advantages such as environmental friendliness, economy, and ease of cleaning.

[0064] In this invention, the lubricating coating material is composed of base powder, deionized water and active additives, and the weight ratio of base powder, deionized water and active additives is (37.6-48.2):(49.1-58.6):(1.3-11.7).

[0065] Preferably, the weight ratio of the base powder, deionized water and active additive is (40-45):(51-55):(2-6).

[0066] Specifically, the base powder consists of the following components by weight percentage:

[0067] (1) 22.8% to 37.2% of graphite powder with a particle size of 500 to 2000 mesh;

[0068] (2) 12.8% to 23.7% molybdenum disulfide powder with a particle size of 1000 to 2000 mesh;

[0069] (3) 16.9%–28.6% silica with a particle size of 800–1500 mesh;

[0070] (4) 11.3% to 20.5% alumina

[0071] (5) 2.6% to 9.3% potassium oxide and sodium oxide;

[0072] (6) 14.6% to 21.9% sodium silicate powder with a modulus of 2.0 to 2.8.

[0073] Furthermore, the active additives are composed of the following components by weight percentage:

[0074] (1) 29.3% to 46.5% wetting agent;

[0075] (2) 31.9% to 41.4% dispersant;

[0076] (3) 11.9% to 21.4% defoamer;

[0077] (4) 7.3% to 16.8% antioxidants.

[0078] The wetting agent includes the following components: sodium hydroxide, amide compounds, and sodium dodecyl sulfate or sodium dibutyl sulfonate, wherein the weight ratio of sodium hydroxide, amide compounds, and sodium dodecyl sulfate or sodium dibutyl sulfonate is (20.1–43.2):(18.7–35.1):(23.6–44.5).

[0079] The dispersant comprises the following components: an ammonium salt solution of modified styrene-maleic acid copolymer, sodium carboxymethyl cellulose or acrylate copolymer, and sodium dodecylbenzene sulfonate or polysulfonate, wherein the weight ratio of the ammonium salt solution of modified styrene-maleic acid copolymer, sodium carboxymethyl cellulose or acrylate copolymer to sodium dodecylbenzene sulfonate or polysulfonate is (34.3–52.6):(11.5–21.9):(27.8–44.2);

[0080] The defoamer includes the following components: carboxyl amide defoamer, polyoxyethylene ether, and silicone defoamer, and the weight ratio of carboxyl amide defoamer, polyoxyethylene ether, and silicone defoamer is (17.6-33.2):(15.2-21.7):(22.8-51.3);

[0081] The antioxidant comprises the following components: sodium thiosulfate, water-soluble L-ascorbic acid, and disodium ethylenediaminetetraacetate or sodium pyrophosphate, wherein the weight ratio of sodium thiosulfate, water-soluble L-ascorbic acid, and disodium ethylenediaminetetraacetate or sodium pyrophosphate is (33.6–58.2):(14.8–28.4):(23.4–43.1).

[0082] Please see Figure 1 The present invention also provides a method for preparing the above-mentioned lubricating coating material, specifically including the following steps:

[0083] Step 1: Synthesis of the base powder: Weigh out 22.8%–37.2% graphite powder, 12.8%–23.7% molybdenum disulfide powder, 16.9%–28.6% silicon dioxide, 11.3%–20.5% aluminum oxide, 2.6%–9.3% potassium oxide and sodium oxide, and 14.6%–21.9% sodium silicate powder as raw materials according to weight percentage; then homogenize the above raw materials to obtain the base powder.

[0084] Step 2, Preparation of active additives: Weigh out 29.3%–46.5% of wetting agent, 31.9%–41.4% of dispersant, 11.9%–21.4% of defoamer, and 7.3%–16.8% of antioxidant as raw materials according to weight percentage; then homogenize the above raw materials to obtain the active additives;

[0085] Step 3, Preparation of lubricating coating material: After heating deionized water to a set temperature, add the base powder synthesized in step 1 and perform homogenization treatment. At the same time, add the active additive prepared in step 2 during the homogenization treatment. During the homogenization treatment, control the weight ratio of the base powder, deionized water and active additive to be (37.6~48.2):(49.1~58.6):(1.3~11.7). After homogenization is completed, stir the resulting liquid thoroughly and cool it naturally to room temperature after stirring. Finally, the anti-oxidation water-based lubricating coating material for hot extrusion is obtained.

[0086] In step 1, a three-dimensional mixer is used to homogenize the base powder. The spindle speed of the three-dimensional mixer is set to 10 rpm to 24 rpm, and the stirring time is set to 1 h to 3 h to fully homogenize the base powder. This avoids segregation, stratification, and agglomeration caused by the different specific gravities of the components during the mixing process.

[0087] In step 2, a top-mounted electric stirrer is used for homogenization of the active additive, and the stirring speed of the top-mounted electric stirrer is set to 50 rpm to 200 rpm, and the stirring time is set to 5 min to 10 min.

[0088] In step 3, the deionized water used has a resistivity of 0.5 MΩ to 18 MΩ at room temperature and is heated to 55℃ to 95℃. A homogenizer is used for homogenization, with the speed set to 15000 rpm to 20000 rpm. Homogenization is carried out for at least 30 minutes, with additives added every 5 to 10 minutes during the homogenization process. The amount of active additive added at one time does not exceed one-third of its total weight. After homogenization, the electric mixer is set to a speed of 100 rpm to 500 rpm and a stirring time of 2 to 4 hours.

[0089] To further verify the effectiveness of the present invention, the inventors conducted the following specific experiments:

[0090] Example 1 (Application of water-based lubricating coating materials in the production of pure zirconium tubes)

[0091] The preparation process of the lubricating coating material in this embodiment is as follows:

[0092] 1) Synthesis of basic powder: Weigh out 23% graphite powder with a particle size of 1500 mesh, 15% molybdenum disulfide powder with a particle size of 1000 mesh, 23% silicon dioxide with a particle size of 1000 mesh, 17% aluminum oxide, 4% potassium oxide, 2% sodium oxide, and 16% sodium silicate powder with a modulus of 2.3 according to the weight percentage. Transfer all of them into a three-dimensional mixer, set the spindle speed to 15 rpm, and stir for 1.5 hours to obtain the basic powder.

[0093] 2) Preparation of active additives: Weigh 33% wetting agent, 41% dispersant, 12% defoamer and 14% antioxidant according to weight percentage, and then transfer them all into a top-mounted electric stirrer. Set the stirring speed to 50 rpm and stir for 10 minutes to obtain uniform active additives.

[0094] The wetting agent comprises sodium hydroxide, amide compounds, and sodium dodecyl sulfate in a weight ratio of 43:19:38; the dispersant comprises modified styrene-maleic acid copolymer, ammonium salt solution of sodium carboxymethyl cellulose, and sodium dodecylbenzene sulfonate in a weight ratio of 52:12:36; the defoamer comprises carboxylamide defoamer, polyoxyethylene ether, and silicone defoamer in a ratio of 28:21:51; and the antioxidant comprises sodium thiosulfate, water-soluble L-ascorbic acid, and disodium ethylenediaminetetraacetate in a weight ratio of 58:15:27.

[0095] 3) Preparation of lubricating coating material: Deionized water with a resistivity of 0.5 MΩ was heated to 75°C. After reaching the temperature, the base powder synthesized in step 1) was added. Homogenization was carried out using a homogenizer (speed set to 15000 rpm) for 40 min. During the homogenization process, an active additive was added every 8 min, with each addition being one-third of the total weight. The weight ratio of the base powder, deionized water and active additive was controlled to be 40:55:5. After homogenization, the mixed liquid was transferred to an electric dispersing stirrer and stirred at 200 rpm for 3 h. After stirring, the mixture was allowed to cool naturally to room temperature to obtain the water-based lubricating coating material.

[0096] The actual application process of the water-based lubricating coating material obtained in this embodiment in the production of pure zirconium tubes:

[0097] A) First, the pure zirconium metal ingot blank is sandblasted to achieve a surface roughness Ra of 3.2 to 6.3 μm. Then, the metal ingot blank is cleaned in an ultrasonic cleaning tank with a metal degreasing agent to improve the bonding strength between the coating and the surface during subsequent lubrication.

[0098] B) The water-based lubricating coating material prepared in this embodiment is placed into a special container, and the pure zirconium ingot blank treated in step A) is completely immersed in it for 3-5 seconds before being removed, so that its surface is uniformly coated with the water-based lubricating coating material. Then, it is dried at room temperature for 3.5 hours and then hot-extruded at a temperature of 700℃. The extruded tube blank has a specification of Ф50×12mm and an extrusion ratio of 12. The pressure is stable during the process, and the surface of the final product is free of obvious defects such as grooves and cracks. Its surface quality is as follows. Figure 6 As shown.

[0099] Furthermore, the inventors conducted friction tests on the pure zirconium tube prepared using the lubricating coating material in Example 1. The test conditions were a high temperature environment of 500℃ to 800℃, performed using a rotary friction and wear testing machine. The final friction coefficient was found to be 0.193 to 0.212. Figure 2 As shown; Figures 3-5 The data and images obtained by white light interference of the wear tracks after the friction and wear test are shown. The wear track width is 1.65 mm and the wear track depth is 0.535 mm. The wear track test results are sufficient to show that the water-based lubricating coating has a good lubrication effect after use, the wear track is relatively smooth, and the substrate material is not exposed.

[0100] Example 2 (Application of water-based lubricating coating materials in Zr-4 pipe production)

[0101] The preparation process of the lubricating coating material in this embodiment is as follows:

[0102] 1) Synthesis of basic powder: Weigh out 28% graphite powder with a particle size of 1500 mesh, 17% molybdenum disulfide powder with a particle size of 1000 mesh, 17% silicon dioxide with a particle size of 1000 mesh, 15% aluminum oxide, 3% potassium oxide, 2% sodium oxide, and 18% sodium silicate powder with a modulus of 2.8 according to the weight percentage. Transfer all of them into a three-dimensional mixer, set the spindle speed to 10 rpm, and stir for 3 hours to obtain the basic powder.

[0103] 2) Preparation of active additives: Weigh 30% wetting agent, 33% dispersant, 21% defoamer and 16% antioxidant according to weight percentage, and then transfer them all into a homogenizer. Set the stirring speed to 200 rpm and stir for 5 minutes to obtain homogenized active additives.

[0104] The wetting agent comprises the following components: sodium hydroxide, amide compounds, and sodium dibutyl sulfonate, in a weight ratio of 21:35:44; the dispersant comprises the following components: modified styrene-maleic acid copolymer, ammonium salt solution of acrylate copolymer, and polysulfonates, in a weight ratio of 35:21:44; the defoamer comprises the following components: carboxylamide defoamer, polyoxyethylene ether, and silicone defoamer, in a weight ratio of 33:20:47; and the antioxidant comprises the following components: sodium thiosulfate, water-soluble L-ascorbic acid, and sodium pyrophosphate, in a weight ratio of 34:23:43.

[0105] 3) Preparation of lubricating coating material: Deionized water with a resistivity of 6 MΩ was heated to 55°C. After reaching the temperature, the base powder synthesized in step 1) was added. Homogenization was carried out using a homogenizer (speed set to 18000 rpm) for 35 min. During the homogenization process, an active additive was added every 5 min, with each addition being one-fifth of the total weight. The weight ratio of the base powder, deionized water and active additive was controlled to be 43:51:6. After homogenization, the mixed liquid was transferred to an electric dispersing stirrer and stirred at 500 rpm for 2 h. After stirring, the mixture was allowed to cool naturally to room temperature to obtain the water-based lubricating coating material.

[0106] The actual application process of the water-based lubricating coating material obtained in this embodiment in the production of Zr-4 pipes:

[0107] A) First, the Zr-4 metal ingot blank is sandblasted to achieve a surface roughness Ra of 3.2 to 6.3 μm. Then, the metal ingot blank is cleaned in an ultrasonic cleaning tank with a metal degreasing agent to improve the bonding strength between the coating and the surface during subsequent lubrication.

[0108] B) The water-based lubricating coating material prepared in this embodiment is placed into a special container. The Zr-4 ingot treated in step A) is then completely immersed in the container for 3-5 seconds and then removed to ensure that the surface is uniformly coated with the water-based lubricating coating material. After drying at room temperature for 3.5 hours, it is hot-extruded at a temperature of 650°C. The extruded tube blank has a specification of Ф80×20mm and an extrusion ratio of 10. The pressure is stable during the process, and the final product has no obvious defects such as grooves or cracks. Its surface quality is as follows: Figure 7 As shown.

[0109] Example 3 (Application of water-based lubricating coating materials in Zr-4 bar production)

[0110] The preparation process of the lubricating coating material in this embodiment is as follows:

[0111] 1) Synthesis of basic powder: Weigh out 33% graphite powder with a particle size of 1500 mesh, 13% molybdenum disulfide powder with a particle size of 1000 mesh, 17% silicon dioxide with a particle size of 1000 mesh, 13% aluminum oxide, 1% potassium oxide, 2% sodium oxide, and 21% sodium silicate powder with a modulus of 2.3 according to the weight percentage. Transfer all of them into a three-dimensional mixer, set the spindle speed to 24 rpm, and stir for 1 hour to obtain the basic powder.

[0112] 2) Preparation of active additives: Weigh 33% wetting agent, 40% dispersant, 12% defoamer and 15% antioxidant according to weight percentage, and then transfer them all into a homogenizer. Set the stirring speed to 400 rpm and stir for 8 minutes to obtain homogenized active additives.

[0113] The wetting agent comprises sodium hydroxide, amide compounds, and sodium dodecyl sulfate in a weight ratio of 42:34:24; the dispersant comprises modified styrene-maleic acid copolymer, ammonium salt solution of sodium carboxymethyl cellulose, and sodium dodecylbenzene sulfonate in a weight ratio of 51:21:28; the defoamer comprises carboxylamide defoamer, polyoxyethylene ether, and silicone defoamer in a ratio of 32:18:50; and the antioxidant comprises sodium thiosulfate, water-soluble L-ascorbic acid, and disodium ethylenediaminetetraacetate in a weight ratio of 48:28:24.

[0114] 3) Preparation of lubricating coating material: Deionized water with a resistivity of 16 MΩ was heated to 95°C. After reaching the temperature, the base powder synthesized in step 1) was added. Homogenization was carried out using a homogenizer (speed set to 20000 rpm) for 32 min. During the homogenization process, an active additive was added every 10 min, with each addition being one-third of the total weight. The weight ratio of the base powder, deionized water and active additive was controlled to be 45:53:2. After homogenization, the mixed liquid was transferred to an electric dispersing stirrer and stirred at 100 rpm for 4 h. After stirring, the mixture was allowed to cool naturally to room temperature to obtain the water-based lubricating coating material.

[0115] The actual application process of the water-based lubricating coating material obtained in this embodiment in the production of Zr-4 bars:

[0116] A) First, the Zr-4 metal ingot blank is sandblasted to achieve a surface roughness Ra of 3.2 to 6.3 μm. Then, the metal ingot blank is cleaned in an ultrasonic cleaning tank with a metal degreasing agent to improve the bonding strength between the coating and the surface during subsequent lubrication.

[0117] B) The water-based lubricating coating material prepared in this embodiment is placed into a special container. The Zr-4 ingot treated in step A) is then completely immersed in the container for 3-5 seconds and then removed to ensure that the surface is uniformly coated with the water-based lubricating coating material. After drying at room temperature for 3.5 hours, it is hot-extruded at a temperature of 600℃. The extruded billet size is Ф100mm, the extrusion ratio is 5, and the pressure is stable during the process. The final product has no obvious defects such as grooves or cracks, and its surface quality is as follows. Figure 8 As shown.

[0118] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention.

[0119] It should be understood that the present invention is not limited to the content already described above, and various modifications and changes can be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. An anti-oxidation water-based lubricating coating material for hot extrusion, characterized in that: The anti-oxidation water-based lubricating coating material for hot extrusion is composed of a base powder, deionized water and an active auxiliary agent, and the weight ratio of the base powder, deionized water and the active auxiliary agent is (37.6-48.2): (49.1-58.6): (1.3-11.7).

2. The anti-oxidation water-based lubricating coating material for hot extrusion according to claim 1, characterized in that: The base powder consists of the following ingredients by weight: (1) 22.8% to 37.2% graphite powder; (2) 12.8% to 23.7% molybdenum disulfide powder; (3) 16.9% to 28.6% silicon dioxide; (4) 11.3% to 20.5% alumina (5) 2.6% to 9.3% potassium oxide and sodium oxide; (6) 14.6% to 21.9% sodium silicate powder; The particle size of the graphite powder is 500-2000 meshes, the particle size of the molybdenum disulfide powder is 1000-2000 meshes, the particle size of the silicon dioxide is 800-1500 meshes, and the modulus of the sodium silicate powder is 2.0-2.

8.

3. The anti-oxidation water-based lubricating coating material for hot extrusion according to claim 1, characterized in that: The active additive is composed of the following ingredients by weight: (1) 29.3% to 46.5% wetting agent; (2) 31.9% to 41.4% dispersant; (3) 11.9% to 21.4% defoaming agent; (4) 7.3% to 16.8% antioxidants.

4. The anti-oxidation water-based lubricating coating material for hot extrusion according to claim 3, characterized in that: The wetting agent comprises the following components: sodium hydroxide, an amide compound and sodium dodecyl sulfate or dibutyl sodium sulfate, and the weight ratio of the sodium hydroxide, the amide compound and the sodium dodecyl sulfate or dibutyl sodium sulfate is (20.1-43.2): (18.7-35.1): (23.6-44.5); The dispersant comprises the following components: modified styrene maleic acid copolymer, ammonium salt solution of sodium carboxymethyl cellulose or acrylate copolymer and sodium dodecyl benzene sulfonate or polysulfonate, and the weight ratio of the modified styrene maleic acid copolymer, ammonium salt solution of sodium carboxymethyl cellulose or acrylate copolymer to sodium dodecyl benzene sulfonate or polysulfonate is (34.3-52.6): (11.5-21.9): (27.8-44.2); The defoamer comprises the following components: a carboxyamide compound defoamer, polyoxyethylene ether and an organosilicon defoamer, and the weight ratio of the carboxyamide compound defoamer, polyoxyethylene ether and organosilicon defoamer is (17.6-33.2): (15.2-21.7): (22.8-51.3); The antioxidant comprises the following components: sodium thiosulfate, water-soluble L-ascorbic acid and disodium ethylenediaminetetraacetate or sodium pyrophosphate, and the weight ratio of the sodium thiosulfate, water-soluble L-ascorbic acid to disodium ethylenediaminetetraacetate or sodium pyrophosphate is (33.6-58.2): (14.8-28.4): (23.4-43.1).

5. A method for preparing an anti-oxidation water-based lubricating coating material for hot extrusion, characterized in that: The following steps are involved: Step 1, synthesis of base powder: according to weight percentage, 22.8% to 37.2% of graphite powder, 12.8% to 23.7% of molybdenum disulfide powder, 16.9% to 28.6% of silicon dioxide, 11.3% to 20.5% of aluminum oxide, 2.6% to 9.3% of potassium oxide and sodium oxide, and 14.6% to 21.9% of sodium silicate powder are weighed as raw materials; then the above raw materials are homogenized to obtain the base powder; Step 2, preparation of active auxiliary agent: according to weight percentage, 29.3% to 46.5% of wetting agent, 31.9% to 41.4% of dispersant, 11.9% to 21.4% of defoaming agent and 7.3% to 16.8% of antioxidant are weighed as raw materials; then the above raw materials are homogenized to obtain the active auxiliary agent; Step 3, preparation of lubricating coating material: after heating deionized water to a set temperature, add the base powder synthesized in step 1, and perform homogenization. At the same time, add the active additive prepared in step 2 during the homogenization process, and during the homogenization process, control the weight ratio of the base powder, deionized water and active additive to be (37.6-48.2): (49.1-58.6): (1.3-11.7); after the homogenization is completed, stir and mix the obtained liquid thoroughly, and cool it naturally to room temperature after stirring, and finally obtain the anti-oxidation water-based lubricating coating material for hot extrusion according to any one of claims 1 to 4.

6. The preparation method according to claim 5, characterized in that: In step 1, a three-dimensional mixer is used for homogenizing the base powder, and the main shaft speed of the three-dimensional mixer is set to 10 rpm to 24 rpm, and the stirring time is set to 1 h to 3 h.

7. The preparation method according to claim 5, characterized in that: In step 2, the active additive is homogenized by an overhead electric stirrer, the stirring speed of the overhead electric stirrer is set to 50 rpm to 200 rpm, and the stirring time is set to 5 min to 10 min.

8. The preparation method according to claim 5, characterized in that: In step 3, the deionized water is deionized water with a resistivity of 0.5MΩ to 18MΩ at room temperature, and the deionized water is heated to a temperature of 55° C. to 95° C.; The homogenization process uses a homogenizer, the speed of the homogenizer is set to 15000rpm-20000rpm, and the homogenization lasts for more than or equal to 30min; After homogenization, the obtained liquid is transferred into an electric dispersing stirrer for stirring. The speed of the electric dispersing stirrer is set to 100 rpm to 500 rpm, and the stirring time is set to 2 h to 4 h.

9. The preparation method according to claim 5, characterized in that: In step 3, during the homogenization process, the active auxiliary agent is added in batches, specifically, once every 5 minutes to 10 minutes, and the single amount of the active auxiliary agent added does not exceed one third of its total weight.

10. An application of the anti-oxidation water-based lubricating coating material for hot extrusion as claimed in any one of claims 1 to 4, or the anti-oxidation water-based lubricating coating material for hot extrusion prepared by the preparation method according to any one of claims 5 to 9 in the hot extrusion of zirconium and zirconium alloys to prepare rods, tubes and profiles.